Mössbauer and xrd analysis of corrosion products of carbonated alkali-activated slag reinforced concretes (2011)
Steel bars embedded in an alkali-activated slag (AAS) concrete have been exposed (after curing for 28 days) to an accelerated carbonation chamber (3 % CO2, 65 % relative humidity (RH), and 25 ºC temperature) and to a laboratory environment (0.03 % CO2, 65 %RH, and 25 ºC). Ordinary Portland cement (OPC) was also tested for comparative purposes and exposed to identical experimental conditions.Corrosion products generated at the steel/concrete interface were characterized using Mössbauer spectrometry and the X-ray diffraction(XRD) technique. The main compounds were magnetite (Fe3O4), wuestite (FeO), and goethite (a-FeOOH). The morphology of corrosionproducts was analyzed using the scanning electron microscopy technique (SEM).